Reclaiming feminism : challenging everyday misogyny - David, Miriam E. (Policy Press, 2016)
"Since the second-wave feminism of the 1970s, women's rights and opportunities in education and employment have increased across the globe. But has equality -- whether social, political, or legal -- really been achieved? Miriam E. David celebrates the achievements of international feminists of the past fifty years and provides a critique of how the expansion of global higher education has masked their pioneering zeal and zest for knowledge. Looking at the changing zeitgeist, David contends that feminism has yet to have an enduring influence, despite the generations of women who have felt empowered. She illustrates the power of patriarchal social relations and shows how everyday sexism and misogyny are still keenly felt."-- Provided by publisher
Keywords: Feminism -- Great Britain -- History.; Misogyny.; Féminisme -- Grande-Bretagne -- Histoire.; Misogynie.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; SOCIAL SCIENCE -- Feminism & Feminist Theory.; Feminism; Misogyny; Great Britain; History